Prevalence and determinants of urinary incontinence among female staff in a public university in Malaysia - Pei, Juin Goh; Hidzer, Nur Hazirah; Elangovan, Lenishaa; Basri, Nurul Iftida; Dasrilsyah, Rima Anggrena (Faculty of Medicine, Universiti Teknologi Mara, 2023)
Urinary incontinence (UI) is a common problem that has become a significant health issue, significantly impacting the daily life of affected individuals. The prevalence of UI in women globally seem to vary widely. This may be due either to the diagnostic criteria used or to under-reporting. Much, therefore, still remains to be reported on the prevalence of urinary incontinence in the various communities around the world. Thus, this study determines the prevalence of urinary incontinence and its associated factors among female staff at Universiti Putra Malaysia (UPM), consisting of a study sample that was derived from the community in the state of Selangor, Malaysia. Methods: A cross-sectional study was conducted among female staff in UPM from 5 – 25, August 2020. A pretested, self-administered questionnaire comprising of two sections was given to the respondents through convenient sampling. The socio-demographic and behavioral characteristics were described using descriptive analysis. Chi-square test or Fisher’s Exact Test were used to analyze the association between risk factors of urinary incontinence and its prevalence. Results: A total of 179 respondents were recruited in the study. The prevalence of urinary incontinence among female staff in UPM was 0.274 (27.4). There was no significant association between age (p=0.285), body mass index (p=0.968), parity (p=0.330) and mode of delivery (p=0.912) for normal vagina delivery, for caesarean section delivery (p=0.413), for assisted vagina delivery (p=0.614) and menopause status (p=0.346) with urinary incontinence among female staff in UPM. Conclusion: The present study suggests that the prevalence of urinary incontinence among female staff in UPM is similar to that in the worldwide population.